The Female FTSE Board Report 2014: Crossing the finish line - Vinnicombe, Susan; Doldor, Elena; Turner, Caroline (Cranfield University, 2014)
This year we have seen three major breakthroughs in FTSE 100 boards: the percentage of women in them has broken the 20% level (20.7%), the number of women on them has exceeded the 200 mark (205) and the number of all male boards has dropped to two. In the past six months the pace of change in appointing women to FTSE boards has increased to 35.5% an FTSE 100 and 33.3% on FTSE 250 boards. Turnover on FTSE 100 boards has risen to the 2012 level of 17% and on that basis our trajectory shows that we should reach 26.7% women on boards by 31 December 2015. Calculating our trajectory on 14% turnover (average pre 2011 turnover) we should still reach the Davies target by 31 December 2015 (25.3%)